2021
DOI: 10.3122/jabfm.2021.04.210044
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship Between Mortality and Eating Breakfast and Fiber

Abstract: Background: Recent studies suggest that intermittent fasting or skipping breakfast may be good strategies for weight loss and better health. The objective of this study was to determine whether regular breakfast is associated with overall or cardiovascular mortality.Methods: Cohort study with follow-up mortality data from the NHANES 1999-2002. National weighted sample. Outcomes were overall and cardiovascular mortality; secondary was fiber intake.Results: Out of 5761 participants, there were 4778 (82.9%) ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…The observed meal skipping prevalence of 19.5% is consistent with similar research in Korean older adults, which noted that 20.9% of participants indicated some level of meal skipping ( 5 ). It is also similar to recent statistics on breakfast skipping in adults, whereby King et al ( 19 ) reported that 17.1% of adults skipped breakfast. However, it differs from the prevalence observed in children (10%) ( 7 ), adolescents (29.9%) ( 20 ) and younger adults (10%) ( 21 ) highlighting the need for age specific research on important dietary behaviours, such as meal skipping.…”
Section: Discussionsupporting
confidence: 90%
“…The observed meal skipping prevalence of 19.5% is consistent with similar research in Korean older adults, which noted that 20.9% of participants indicated some level of meal skipping ( 5 ). It is also similar to recent statistics on breakfast skipping in adults, whereby King et al ( 19 ) reported that 17.1% of adults skipped breakfast. However, it differs from the prevalence observed in children (10%) ( 7 ), adolescents (29.9%) ( 20 ) and younger adults (10%) ( 21 ) highlighting the need for age specific research on important dietary behaviours, such as meal skipping.…”
Section: Discussionsupporting
confidence: 90%
“…A cohort study from the NHANES (1999)(2000)(2001)(2002) showed a significant association between eating breakfast and lower all-cause and CVD mortality rates and the significant role of fiber intake; there was no association between fiber and mortality rates in non-breakfast eaters. In addition, this study also showed that breakfast eaters with high daily total fiber intake had lower all-cause mortality risks compared to their counterparts with low fiber intake, but this association was not significant for CVD mortality risk [35]. This indicates that breakfast-eating status has an important role in the association between fiber intake and mortality risk.…”
Section: Discussionmentioning
confidence: 60%
“…The European Food Safety Authority and the UK Scientific Advisory Committee on Nutrition recommend a daily fiber intake of 25 g/day and 30 g/day for adults, respectively [ 22 ]. The American Heart Association recommends a dietary fiber intake of at least 25 g/day for adults [ 23 ]. In this study, we divided the participants into two groups based on the fiber intake value of 25 g/day: low-level group (≤25 g/day) and high-level group (>25 g/day).…”
Section: Methodsmentioning
confidence: 99%